Investigation of fluoride pollutant removal from wastewater - Ko, Sin Yee (2024)
Recently, the iron and steel, semiconductor and copper industries have discharged significant amount of wastewater that contains high amount of fluoride into the water system. Several methods can be used to remove fluoride from wastewater to fulfil the discharge requirements, such as reverse osmosis, electrocoagulation, and adsorption. Coagulation is one of the most commonly used method in the industry as it has simple and low operation cost. Response Surface Methodology (RSM) was applied to investigate the fluoride removal from wastewater by using three different coagulants (aluminium sulfate, ferric chloride, and PAC) under different pH and coagulant dosage. Two parameters including pH (3-11) and coagulant dosage (30 %v/v –70 %v/v) were investigated and optimized to obtain the best response of fluoride removal. Poly Aluminium Chloride is found to have the highest fluoride removal, which is 96.5 % under the optimum condition of pH 7 and coagulant dosage of 50 %v/v (2500 mg/L). Aluminium sulfate has the same optimum condition as PAC, but aluminium sulfate has lower fluoride removal, which is 95 %. The sludge mass produced by PAC is 0.0672 g. This is lower than the mass of the sludge produced by aluminium sulfate, which is 0.5538 g. The optimum treatment condition of each coagulants were applied into real industrial wastewater. The result shows that PAC has the highest fluoride removal, 85.13 % with the lowest mass of sludge formation, 0.1364 g. By conducting this study, the coagulant that has high fluoride removal with low sludge formation can be found. Besides that, the treated wastewater will be able to protect the environment and contribute to the achievement of SDG 6. In addition, the fluoride in the wastewater produced by semiconductor, iron and steel, and copper industries can be removed.